Implementation of Compensation Claim's Mechanism through Pretrial for Error in Persona in the Criminal Justice System - Feryando Feryando (Ius Poenale, 2021)
An error in persona in the implementation of the criminal justice system is a type of destructive action by law enforcement officers that can cause harm to someone. The use of authority by investigators to arrest and detain and detention and prosecution by public prosecutors is a concrete form of persona error. This study focused on the mechanism of a compensation claim through pre-trial due to a persona error in implementing the criminal justice system and an impediment to the implementation of the pre-trial judge's decision on the granting of the compensation claim. The method used is normative and empirical juridical research. The results showed that the mechanism of a claim for compensation through pre-trial due to an error in person in implementing the criminal justice system was carried out fundamentally at the formulation stage. These formulations outlined in the Code Of Criminal Procedure (Kitab Undang-Undang Hukum Acara Pidana/ KUHAP) and Government Regulation Concerning Implementation of The Book of Criminal Procedure Law as a basis for the implementation of pre-trial and the application stage. The statutory factors of Decree of the Minister of Finance of the Republic of Indonesia Number: 983 / KMK.01 / 1983 (Keputusan Menteri Keuangan RI Nomor 983/KMK.01/1983) are an impediment in implementing the pre-trial judge's determination of the compensation claim because the regulation governs administrative procedures that are lengthy and involve government agencies.